An Assessment of Developing the Human Capital in Supply Chains Across Borders and Cultures in U.S. and Russia and CIS Government Programs - Thor Eric; Olga Panteleeva (European Regional Science Association (ERSA), 2003)
This article outlines and assesses the training and education programs focusing on rural and regional human capital development in 'supply and business Chains'. Today's rural managers and educators must be trained and educated to operate across national boundaries and differing economic, financial and social systems. The article focuses on the training and education in the U.S. Government's Cochran Fellowship Program. It compares it to the European counter parts This program began in 1984 and vastly expanded in the early 1990's as Russia and the CIS countries emerged from the communist command oriented 'supply and business chain? systems. Both the East and West have much to gain by improving the human capital in supply chain human management. This means that the human capital must be trained and educated in new technology, transportation systems, planning processes, and trade related issues from differing systems. Rural Mediation and other training and education technigues across cultures, educational backgrounds will also be highlighted. This article looks ahead to the human capital needs in European regional systems and what is needed to bring the current system up to worldwide standards.
Keywords: 330